PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH (STUDI KASUS PADA PD. BPR BKK BOJA CABANG PATEBON KENDAL) - Reny Sukawati (Universitas Diponegoro, 2012)
Govermance Corporation of Loan Public Bank BKK BOJA of Kendal Patebon Branch is goverman corpuration which run banking sector. Development of bank average in Kendal is fast, it causes hard competition. It also causes PD. BPR BKK BOJA of Kendal Patebon Branch increase it’s service quality for getting costumer’s as much as it can. This analysis result show that tangible variable tangible, reliability, responsiveness, assurance and emphaty influence positive and significance of PD. BPR BKK BOJA of Kendal Patebon Branch.